A bidirectional resonant converter based on wide input range and high efficiency for photovoltaic application - Ibrahim Alhamrouni; M. R. Bin Hamzah; Mohamed Salem; Awang Jusoh; Azhar Bin Khairuddin; Tole Sutikno (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This work highlights a modular power conditioning system (PCS) in photovoltaic (PV) applications which consists with a DC-DC converter. The converter is able to regulate and amplify the input DC voltage produced by the PV panal. The implementation of Mosfet as bidirectional switch on the converter yields greater conversion ratio and better voltage regulation than a conventional DC-DC step up converter and PWM resonant converter. It also reduces the switching losses on the output DC voltage of the converter, as the MOSFET switches on primary winding of converter switch on under ZVS conditions. The proposed resonant converter has been designed, with the modification of series resonant converter and PWM boost converter that utilizes the high frequency of AC bidirectional switch to eliminate the weaknesses of used converters. The topology of the proposed converter includes the mode of operations, designing procedure and components selection of the new converter elements. This topology provides a DC output voltage to the inverter at range of about 120Vac-208 Vac.